Biological Validation and Observations of Formaldehyde Fumigation in Operational and Representative Scenarios in High-Containment Laboratories. (March 2020) - Tearle, Jason; MacRae, Gary; Andrews, Spencer; Clarke, Anthony; Stuart, Jamie; Tremblay, Gilles
Introduction: The effectiveness of formaldehyde as a fumigant in laboratories, for equipment, and for containment barrier decontamination applications was assessed, in particular the ability to reproduce biological inactivation (6-log reduction) of commercially available rapid biological indicators in representative operational scenarios and their relative sensitivity to other biological and chemical indicators. Objectives: The primary objective of this study was to describe observations and results of formaldehyde fumigation efficacy in high-containment laboratories. Results: Biological indicators placed throughout laboratory spaces, including ventilation ductwork at distances up to 15 meters, inside pieces of equipment and in lengths of pipe, were mostly negative, demonstrating the ability of formaldehyde to reach the interior and external surfaces tested. Dwell times as short as 10 minutes were shown to be sufficient in barrier decontamination equipment for the fumigation of personal computers. Furthermore, a pipework bore:length ratio of 1:1500 was proven too great a challenge. Indicators placed after extracting HEPA filters in microbiological safety cabinets (MBSCs) were also successfully fumigated (at room temperature) relying solely on diffusion and in the cabinet workspace at 10°C to 12°C. In addition, pressures of up to 900 Pa were experienced in low-leakage laboratory spaces during fumigation. Conclusions: Formaldehyde fumigation was shown to be effective in a variety of scenarios representing operational activities thereby giving process assurance.